Determinants of VIA Test Acceptance among Women of Reproductive Age at Padang Pasir - Putri Aqischa Cahyani; Aladin Aladin; Husna Yetti (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Visual Inspection with Acetic Acid (VIA) is an early detection method for cervical precancerous lesions. VIA coverage in Indonesia remains low. This study aimed to analyze the association of sociodemographic factors, information sources, and husband’s support with VIA test acceptance among women of reproductive age at Padang Pasir Health Center, Padang City. Method: An analytic observational study with a cross-sectional design was conducted in December 2023. The population consisted of women of reproductive age in the working area of Padang Pasir Health Center. A total of 100 respondents were selected using consecutive sampling. Data were collected through structured interviews with questionnaires and analyzed statistically. Result: The analysis revealed no significant association between age, education, occupation, or socioeconomic status and VIA acceptance. In contrast, information sources and husband’s support were significantly associated with acceptance. No significant relationship was found between acceptance and actual participation in VIA screening. Conclusion: Sociodemographic factors did not influence VIA acceptance. Information access and husband’s support were key determinants of willingness to undergo VIA testing. Strengthening health promotion and involving husbands in cervical cancer prevention programs are recommended strategies to increase VIA coverage.